Copper/Silver Bimetallic Nanoparticles Supported on Aluminosilicate Geomaterials as Antibacterial Agents - Rubio-Campos, M; Azocar-Guzman, M; Azocar-Guzman, M; Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (American Chemical Society, 2022)
This study aims to understand how properties of modified aluminosilicate geomaterials influence the antibacterial performance of nanocomposites when prepared with bimetallic nanoparticles (NPs). Copper/silver (Cu/Ag) bimetallic NPs were synthesized in the presence of imogolite (Imo), montmorillonite (Mtt), or zeolite (Zeo) using a simple one-pot method and characterized for their crystal phases, micro- and nanomorphologies, particle size, elemental composition, and electrophoretic mobility. The antibacterial activity was evaluated through minimum inhibition concentration assays of NPs and nanocomposites for Gram (−) Escherichia coli and Gram (+) Staphylococcus aureus bacteria. Deposition of metallic Cu0, Ag0, and cuprite NPs was confirmed in Zeo_Cu/Ag and Imo_Cu/Ag nanocomposites, whereas only Cu0 and Ag0 were identified in Mtt_Cu/Ag. The bimetallic NPs were more uniformly distributed on Zeo and Mtt than Imo. Particle sizes of 28.1 ± 5.0, 9.4 ± 2.3, 10.1 ± 1.7, and 12 ± 1.3 nm were determined for Cu/Ag NPs, Imo_Cu/Ag, Mtt_Cu/Ag, and Zeo_Cu/Ag, respectively. The release rate of Cu and Ag ions from Zeo_Cu/Ag was higher than those of pristine Cu/Ag NPs and the other two nanocomposites. The antimicrobial action of bimetallic NPs and nanocomposites was dose-dependent in relation to the concentration of concerned materials and their stability in the medium. The physicochemical characteristics of Zeo resulted in a homogeneous distribution and low oxidation and agglomeration of Cu/Ag NPs, consequently increasing the antibacterial activity. Results of this study highlight the benefits of using a geomaterial support to achieve high antibacterial activity of bimetallic NPs, which could help reduce the consumption of pure Cu/Ag salts in NP-based antibacterial applications. © 2022 American Chemical Society